SUBCLONING AND EXPRESSION OF HALOACID DEHALOGENASE GENE FROM Klebsiella pneumoniae ITB1 IN pET-hakp1 IN E. coli BL21(DE3) - RINO ANGGORO (NIM: 20515018), RIDANI
Organohalogen comprise a major compound used in manufactures of dyes, plastics, drugs, pesticides, and other industrial products. The waste of these compounds are persistence and stable, therefore become environmental pollutants. These compounds are also possible to be transformed into other toxic metabolites to human and other organisms, therefore the degradation and detoxication of these compounds is very important. Such degradation may occur via enzymatic dehalogenation catalyzed by haloacid dehalogenase, particularly for haloacid compounds. The haloacid dehalogenase gene from Klebsiella pneumoniae ITB1 (named hakp1) has been previously isolated and characterized on pGEM-T. This research aimed to subcloned the hakp1 gene into pET-30a(+) expression vector to further improve and analyze its expression. Specific primer for subcloning was designed with addition of restriction sites to get a correct orientation of subcloning. The designed primers were 5'-GAATTCATGATCCGCGCCATCGTG-3' as forward primer and 5'-AAGCTTTCATGCTGGGATCTGCTCC-3' as reverse primer with addition of EcoRI and HindIII recognition sites respectively. These restriction sites were added based on the nucleotide sequences and restriction sites that were not present in hakp1 gene, but possesed on multiple cloning site on pET-30a(+). Amplification of hakp1 gene was performed by PCR using the chromosome of Klebsiella pneumoniae ITB1 as template, produced 0.7 kb amplicon. This fragment was ligated into pGEM-T vector, transformed into competent E. coli TOP10, and selected by blue-white screening method to produce pGEM-hakp1 recombinant. The hakp1 fragment on pGEM-hakp1 was then subcloned into pET-30a(+) expression vector employing the two created restriction sites, transformed into E. coli BL21 (DE3), and selected by kanamycine medium to obtained pET-hakp1 recombinant clone. The pGEM-hakp1 and pET-hakp1 recombinant plasmids were isolated, confirmed by size screening, restriction analysis, re-PCR, and sequencing. The size of hakp1 gene is 690 bp. Expression of pET-hakp1 in E. coli BL21(DE3) was induced by IPTG. The SDS-PAGE analysis of cell lysate showed that the molecular weight of haloacid dehalogenase (Hakp1) protein was around 30 kDa. Zymogram analysis using monochloroacetic acid (MCA) as substrate and AgNO3 as reagent produced AgCl white precipitate, indicated that Hakp1 has dehalogenase activity. Quantitative assay of Hakp1 gave specific activity of 84.29 U/mg on 40oC at pH 9. One unit of haloacid dehalogenase activity was defined as the amount of enzyme that catalyzed the formation of 1 μM chloride ion per minute. Predicted three-dimensional structure of Hakp1 using SWISS-MODEL and I-TASSER showed α/β motif folding which comprised of cap and core domain. The possible active sites of Hakp1 were Asp8, Glu10, Leu22, Phe23, Trp90, Ser125, Ser126, and Lys159 as determined using Sequence Annotated by Structure and AutoDock Vina.